Duodenal gastrointestinal stromal tumor: case report and importance of ecoendoscopy - Santos, Brian França dos (2021)
Gastrointestinal stromal tumors (GISTs) are generally quite rare, but the same are the mesenchymal neoplasms that are most frequently identified in the gastrointestinal tract (GIT) and represent 0.1 to 3% of all gastrointestinal tumors. The diagnosis of this pathology is made according to the clinical picture, in the morphological characteristics, and fundamentally in the consideration of the presence of the protein c-KIT (CD117) detected by immunohistochemical method. In most cases, these tumors present in the individual asymptomatically, so they are discovered incidentally by imaging exams. The prognostic factors of great importance are the size of the tumor and the mitotic index. Surgical resection is the therapy of choice and imatinib mesylate chemotherapy, which is indicated in cases of unresectability or metastatic disease. We present a case of Duodenal GIST diagnoses by echoendoscopy after an incidental finding during an upper gastrointestinal endoscopy exam.